3x+3y-6y+6x=

Simple and best practice solution for 3x+3y-6y+6x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+3y-6y+6x= equation:


Simplifying
3x + 3y + -6y + 6x = 0

Reorder the terms:
3x + 6x + 3y + -6y = 0

Combine like terms: 3x + 6x = 9x
9x + 3y + -6y = 0

Combine like terms: 3y + -6y = -3y
9x + -3y = 0

Solving
9x + -3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3y' to each side of the equation.
9x + -3y + 3y = 0 + 3y

Combine like terms: -3y + 3y = 0
9x + 0 = 0 + 3y
9x = 0 + 3y
Remove the zero:
9x = 3y

Divide each side by '9'.
x = 0.3333333333y

Simplifying
x = 0.3333333333y

See similar equations:

| 2.3v=13.5 | | 30x^2-25-30=0 | | 0.667(3x-9)=4(x+6) | | (10n+1)(10n+1)= | | 20(20)= | | 15y/3x-10/3x=6 | | -11+n=-13 | | 15y-10/3x=6 | | -0.667(6-2a)=6 | | 3x-7=138+8x | | 81x^2+36xv+4v^2=0 | | x/-5.7=9.1 | | 36/2m+3=4 | | 3[4x-(6-5x)]=15-6(5-2x) | | 15=80-4q | | =85+36 | | 10a-2= | | 2(3a-2)+4a= | | 2(3a-2)+4ab= | | -2x+15=43-5x | | x/-4-5=4 | | 6x-14=4x+4 | | 8x=15+4x | | 22+2=4 | | 3x=-4+(4x-1) | | -1/2m-3=9 | | A=3.14r | | 0.25y+19/2 | | 3y=702 | | 1/4y+91/2 | | 12x^2+9x^2=0 | | (cos)x=1 |

Equations solver categories